The persuasion handbook : developments in theory and practice - Pfau, Michael, 1945-2009; Dillard, James Price (Thousand Oaks, Calif SAGE Publications, 2002)
The Persuasion Handbook provides readers with cogent, comprehensive summaries of research in a wide range of areas related to persuasion. From a topical standpoint, this handbook takes an interdisciplinary approach, covering issues of interest to interpersonal and mass communication researchers as well as psychologists and public health practitioners.
Keywords: Persuasión (Psicología) -- Aspectos sociales; Persuasión (Retórica); Libros electrónicos